2015
DOI: 10.1186/s12913-015-0745-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuity of care on hospital admission in patients with type 2 diabetes: analysis of nationwide insurance data

Abstract: BackgroundA system for managing chronic disease including diabetes mellitus based on primary care clinics has been used in Korea since April 2012. This system can reduce copayments for patients that are managed by a single primary-care provider and lead to improve continuity of care. The aim of this study is to determine whether there is an association between continuity of care for outpatients and hospital admission and identify the continuity index that best explains hospital admissions for patients with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 30 publications
2
45
1
Order By: Relevance
“…Severity of diabetes was not properly considered; this research instead applied the Charlson comorbidity score to consider the patient's overall health condition. In the study by Cho et al [30], the prescription of hypoglycemic agents (types and number) and comorbidity index together were used to consider the severity of the disease. In this study, prescriptions of hypoglycemic agents and comorbidity score were also considered to adjust for the severity of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severity of diabetes was not properly considered; this research instead applied the Charlson comorbidity score to consider the patient's overall health condition. In the study by Cho et al [30], the prescription of hypoglycemic agents (types and number) and comorbidity index together were used to consider the severity of the disease. In this study, prescriptions of hypoglycemic agents and comorbidity score were also considered to adjust for the severity of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the medical institutions, such as types, ownership, number of beds, and number of physicians, were based on the most visited medical institutions during the continuity observation period. According to previous studies [28][29][30], the most visited medical institution was defined as the main medical institution during the continuity observation period. However, if there were medical institutions that had identical frequencies of visits in the same year, the most recently visited medical institution was defined as the main one.…”
Section: Measures and Variablesmentioning
confidence: 99%
“…The effects of continuity of care have been debated in previous studies because some have concluded that continuity of care is associated with fewer hospitalizations, emergency department visits, and hospital admissions [37]; low pharmaceutical expenditures and healthcare expenses [5, 8–10]; decreased mortality rates [11, 12]; fewer duplicated medications [13]; improved medication adherence [14]; and patient satisfaction [15–18]. However, others insist that high continuity of care may lead to the purchase of more drugs overall and that the effects on HRQoL are unclear; thus, these should be further examined [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…The HARP tool was developed by the WestBay Alliance and Western HARP Consortium, and is based on the Chronic Condition Risk Calculator. For example, recently, an integrated primary-secondary model of care for the management of T2D that provided multidisciplinary specialist care in general practice was found to reduce potentially preventable diabetes-related hospital presentations to hospital by approximately half 16 and in addition, improved continuity of care 17 and a primary-care-based empowerment programme were also effective. In addition, dedicated services, such as the Victorian HARP, have been implemented that address the risk of hospitalisation in patients with chronic illness, through coordinating access to services and improving patients' capacity for self-care and maintenance of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the drivers of increased risk of unplanned presentation to hospital may lead to targeted education or treatment strategies designed to mitigate risk or referral into specific management pathways to access additional services. For example, recently, an integrated primary-secondary model of care for the management of T2D that provided multidisciplinary specialist care in general practice was found to reduce potentially preventable diabetes-related hospital presentations to hospital by approximately half 16 and in addition, improved continuity of care 17 and a primary-care-based empowerment programme were also effective. 18 Further research on the outcomes of patients with T2D following attendance at services recommended by the HARP tool, to determine their impact on reducing the risk of hospital presentation, would be of significant importance in assessing the utility of the HARP tool in preventing unplanned hospital presentations.…”
Section: Harp Tool and Hospitalisations In T2dmentioning
confidence: 99%